The role of Islamic education in the development of Islamic civilization - Shogar, Ibrahim Adam Ahmed (2018)
Etymologically, the word education means process of leading or bringing up. According to social perspective, education is “a social function that securing direction and development in the immature through their participation in the life of the group to which they belong”. John Dewey believes that “When we have the outcome of the process in mind, we speak of education as shaping, forming, molding activity—that is, a shaping into the standard form of social activity. When we have the outcome of the process in mind, we speak of education as shaping, forming, molding activity—that is, a shaping into the standard form of social activity. Based on literal meaning, S. M. N. al-Attas defines education as “a process of instilling something into human being”